ENACTING THE POLITICS OF CARE WITH CHRONIC AND CRIP TECHNOLOGIES - Rentschler, Carrie Ann; Nothwehr, Benjamin; Morena, Nina; Mulvin, Dylan; McKinney, Cait; Horrocks, Stephen (AoIR Selected Papers of Internet Research, 2023)
Drawing from feminist and queer technoscience studies, this panel examines the constitutive entanglements of bodies, technologies and systems in Type 1 diabetic continuous glucose monitoring and the intimate feeling of their numbers and data visualization; in the selfie politics of mastectomies on Instagram and the platform vernaculars people use to make the grief of breast cancer’s gendered loss representable; in the ways Bay Area Deaf AIDS activists in the 1980s and 1990s remediated their access to information through infrastructures of care they built for themselves and others; and in the ways Type 1 diabetics navigate the material culture of insulin pump treatment and the politics of diabetic care as both compulsory and liberating. Thinking across their research on chronic and crip technologies, this panel interrogates what it means, and is, to care for oneself and others in relation to the feel of navigating technologized, datafied, and materially marked lives and the systems and communities that shape their very possibilities. Building on Hamraie and Fritsch’s (2019) conception of “crip technoscience” and capacious notions of care articulated by folks in our research, panelists examine how chronic and disabled lives are lived between “enclosed regimes of self-care” with their individualizing models of selfhood and “collective communal care” frameworks (Sharma, 2017, para. 20, para. 4) that our research shows often require new ways of thinking about and better sourcing social and technological infrastructures that are centered around chronic and crip ways of living.